2022
DOI: 10.1001/jamanetworkopen.2021.44386
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Caregiver Experiences With and Perceptions of Risk Evaluation and Mitigation Strategy Programs With Elements to Assure Safe Use

Abstract: IMPORTANCEThe US Food and Drug Administration (FDA) Amendments Act of 2007 authorized the FDA to impose safety requirements on drugs with important risks, such as prescriber certification or routine laboratory testing, to ensure that the benefits of use outweighed the risks. However, little is known about patient and caregiver experiences with these Risk Evaluation and Mitigation Strategy (REMS) programs with Elements to Assure Safe Use (ETASU). OBJECTIVE To understand patient and caregiver experiences with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Across all REMS programs, just over half of physicians reported that the safe use requirements delayed patients in getting their medications. Problems with access have also been reported by patients 23 . To better integrate REMS programs into clinical workflows, the FDA has partnered with the MITRE Corporation for the development of a “proof‐of‐concept prototype,” incorporating REMS activities into standard health information technologies 24 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Across all REMS programs, just over half of physicians reported that the safe use requirements delayed patients in getting their medications. Problems with access have also been reported by patients 23 . To better integrate REMS programs into clinical workflows, the FDA has partnered with the MITRE Corporation for the development of a “proof‐of‐concept prototype,” incorporating REMS activities into standard health information technologies 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Problems with access have also been reported by patients. 23 To better integrate REMS programs into clinical workflows, the FDA has partnered with the MITRE Corporation for the development of a "proof-of-concept prototype, " incorporating REMS activities into standard health information technologies. 24 Routine re-evaluation of REMS programs can help determine whether to remove certain safe use requirements.…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations
“…For secondary prevention, the heightened frequency of testing before treatment initiation and during the first month of treatment for some REMS may pose cost and access issues for patients without meaningfully contributing to risk mitigation [ 25 ]. In addition to streamlining these testing requirements, REMS should ensure that females are effectively counseled on emergency contraception and provided with take-home materials to foster patient autonomy in minimizing teratogenic risks.…”
Section: Teratogenic Riskmentioning
confidence: 99%